False Friends: Exploring Challenges and Opportunities for the Translators - Tušek, Jelena (Array, 2010)
The paper focuses on some of the challenges translators encounter in the new economy. The objective is to show how translators' competitiveness could be increased by incorporating specific semantic issues in programs for machine translation. Emphasis will be on the problem of false friends (or faux amis) as the pairs of words in two languages that look and/or sound similar, but partially or completely differ in meaning. Due to complexity of the issue, false friends present a serious problem for translators, especially in the contemporary economy where a demand for delivering translation in a timely manner is as important as the quality of the translation itself. The comparative analysis of Slovenian and Croatian, as genetically closely related languages belonging to the western group of South Slavic languages, shows the great number of inter- language homonyms in the two languages. Aim of the analysis of false friends is to provide a typology of false friends for the specific language pair that could have an application in machine translation programs.